Group of women. - Unknown:::Creator::::::::::::
Marion Thompson, Esther McCumbre, Grace Mason Joy [or possibly Fry], Helen Denhard Neibel [possibly crossed out], M.G. Alexander in dresses and wearing hats. The first and last ladies have on badges and the third from the right holds papers, in her hands.